Reorientation of the University Intercultural Education in Mexico. Antecedents and Critical Questionings - Garduño, Everardo (Revista Española de Antropología Americana, 2024)
In the year 2020, the Mexican government made it known a document to reorient the university intercultural education and take distance itself from the intercultural policies of the former administrations. The arguments in that text are with no doubt, founded and widely exposed. However, in the analysis of this document, during the process to create the first intercultural university of the so-called "Cuarta Transformación" (Fourth Transformation), this is the Intercultural University of Baja California; the Academic Advisory Group and the Management Group of this project exposed some critical questionings. In this paper I expose five of the most problematic: the direct relationship between the concept of pluridiversity and ethnic-cultural diversity and, in essence, with the national-Indigenous diversity which is reduced to the ethnolinguistic diversity and at last, to the poorest people in Mexico. Other critical questions are made here from the perspective of nomadism as a lifestyle, as well as an epistemic point of view. Particularly, these questionings are about the idea on Indigenous people as Mesoamerican community people, and the Indigenous epistemology as Mesoamerican community grounded.